ETNOZOOLOGI SUKU ANAK DALAM (SAD) KAMPUNG KEBUN DUREN DESA LANTAK SERIBU KECAMATAN RENAH PAMENANG KABUPATEN MERANGIN PROVINSI JAMBI - Mutia Yuli Farida; J Jumari; Fuad Muhammad (Jurnal Akademika Biologi, 2014)
The people of Suku Anak Dalam (SAD) have a very strong interaction with animals due to their hunting tradition. The objective of this study is to describe their knowledge on the varieties of animals which are employed by the society in their daily lives. The research was conducted in Desa Lantak Seribu, Kecamatan Renah Pamenang, Kabupaten Merangin, Provinsi Jambi. The data was collected through explorative method, which included inventorying varieties of animals known by the people and how they utilized the animals. Etnozoology as data collecting method was developed by participative etnobotany; consisted of open ended interview, participative observation, and getting involved in the society’s activities. From the data collected by inventorying and interviewing, the data were tabulated and categorized based on the animals’ utilization. Based on the findings, there are 80 kinds of animals used by the people of Suku Anak Dalam (SAD) and they were categorized into 7 classes; they are Mollusca (4), Arthropod (12), Amphibian (3), Reptiles (8), Pisces (2), Aves (35), and Mammals (15). Based on its utilization, there are: for food (45), for pet (17), for traditional ritual (2), mythical animals (5), as the source of calcium (4), wild animals (5), for medical purposes (3), and pests (6). The people have their own local wisdom on how they employ and manage the varieties of animals they know. Keywords      : Desa Lantak Seribu, Etnozoology, Suku Anak Dalam (SAD)